Direct 3D bioprinting of prevascularized tissue constructs with complex microarchitecture. (April 2017) - Zhu, Wei; Qu, Xin; Zhu, Jie; Ma, Xuanyi; Patel, Sherrina; Liu, Justin; Wang, Pengrui; Lai, Cheuk Sun Edwin; Gou, Maling; Xu, Yang; Zhang, Kang; Chen, Shaochen
Abstract: Living tissues rely heavily on vascular networks to transport nutrients, oxygen and metabolic waste. However, there still remains a need for a simple and efficient approach to engineer vascularized tissues. Here, we created prevascularized tissues with complex three-dimensional (3D) microarchitectures using a rapid bioprinting method – microscale continuous optical bioprinting (μCOB). Multiple cell types mimicking the native vascular cell composition were encapsulated directly into hydrogels with precisely controlled distribution without the need of sacrificial materials or perfusion. With regionally controlled biomaterial properties the endothelial cells formed lumen-like structures spontaneously in vitro . In vivo implantation demonstrated the survival and progressive formation of the endothelial network in the prevascularized tissue. Anastomosis between the bioprinted endothelial network and host circulation was observed with functional blood vessels featuring red blood cells. With the superior bioprinting speed, flexibility and scalability, this new prevascularization approach can be broadly applicable to the engineering and translation of various functional tissues.